Proximal Type - Epithelioid Sarcoma- A Rare And Aggressive Soft Tissue Neoplasm. (28th October 2020) - Zaheer, S; Xu, K; Shakil, F
Abstract: Introduction/Objective: Epithelioid Sarcoma is a rare malignant soft tissue neoplasm that is well known for local recurrence, regional lymph node involvement, and metastasis. It accounts for less than one percent of all sarcomas. Two subtypes of epithelioid sarcoma are described: the conventional or classic subtype and the proximal subtype, with the classic type being more common than the proximal type. We present a case of proximal epithelioid sarcoma involving the inguinal region, in which the patient presented with the history of weight loss for one year and a slow- growing inguinal mass for the last few months. The biopsy was done in an outside hospital and showed carcinoma of unknown origin. Imaging also failed to reveal any clear source of this mass. Methods: The mass was resected and sent to pathology, where H&E staining and immunohistochemistry was done for diagnosis. Results: The H&E sections of the left inguinal mass showed proliferation of large epithelioid cells with a moderate amount of cytoplasm, vesicular nuclear chromatin and prominent nucleoli. Mitosis was also seen. Necrosis was not identified. Immunohistochemical staining was done and revealed that the tumor cells were immunoreactive for epithelial marker cytokeratin AE1/AE3 and showed loss of INI-1. Tumor cells were also negative for Myogenin, ERG, HMB-45, MART-1, Myo-D1, S100, and SMA. Considering the cytomorphology and immunophenotypic findings the diagnosis of epithelioid sarcoma, proximal type was made. Conclusion: Epithelioid sarcoma is a malignant mesenchymal neoplasm with epithelioid cytomorphology and phenotype. Among the two types of epithelioid sarcoma, the proximal type is reported about 50% less than the classic type and is associated with aggressive behavior and worse prognosis. The classic cytomorphology and immunohistochemistry findings helped us in making the diagnosis in this case.